Answer: ![x](https://tex.z-dn.net/?f=x%3C3%5Cfrac%7B175%7D%7B222%7D)
Step-by-step explanation:
![1\frac{1}{5}x-2\frac{1}{3}](https://tex.z-dn.net/?f=1%5Cfrac%7B1%7D%7B5%7Dx-2%5Cfrac%7B1%7D%7B3%7D%3C%5Cfrac%7B1%7D%7B7%7Dx%2B1%5Cfrac%7B1%7D%7B2%7D)
Add
on both sides and subtract
on both sides to leave x's on the left side and independent values on the right.
![(2\frac{1}{3}-\frac{1}{7}x) +1\frac{1}{5}x-2\frac{1}{3}](https://tex.z-dn.net/?f=%282%5Cfrac%7B1%7D%7B3%7D-%5Cfrac%7B1%7D%7B7%7Dx%29%20%2B1%5Cfrac%7B1%7D%7B5%7Dx-2%5Cfrac%7B1%7D%7B3%7D%3C%5Cfrac%7B1%7D%7B7%7Dx%2B1%5Cfrac%7B1%7D%7B2%7D%2B%282%5Cfrac%7B1%7D%7B3%7D-%5Cfrac%7B1%7D%7B7%7Dx%29)
![1\frac{1}{5}x-\frac{1}{7}x](https://tex.z-dn.net/?f=1%5Cfrac%7B1%7D%7B5%7Dx-%5Cfrac%7B1%7D%7B7%7Dx%3C1%5Cfrac%7B1%7D%7B2%7D%2B2%5Cfrac%7B1%7D%7B3%7D)
Solve the fractions.
![1(\frac{1}{5}-\frac{1}{7})x](https://tex.z-dn.net/?f=1%28%5Cfrac%7B1%7D%7B5%7D-%5Cfrac%7B1%7D%7B7%7D%29x%3C1%2B2%28%5Cfrac%7B1%7D%7B2%7D%2B%5Cfrac%7B1%7D%7B3%7D%29)
![1(\frac{(1)(7)-(5)(1)}{(5)(7)} )x](https://tex.z-dn.net/?f=1%28%5Cfrac%7B%281%29%287%29-%285%29%281%29%7D%7B%285%29%287%29%7D%20%29x%3C3%28%5Cfrac%7B%281%29%283%29%2B%282%29%281%29%7D%7B%282%29%283%29%7D%20%29)
![1(\frac{7-5}{35} )x](https://tex.z-dn.net/?f=1%28%5Cfrac%7B7-5%7D%7B35%7D%20%29x%3C3%28%5Cfrac%7B3%2B2%7D%7B6%7D%20%29)
![1(\frac{2}{35} )x](https://tex.z-dn.net/?f=1%28%5Cfrac%7B2%7D%7B35%7D%20%29x%3C3%28%5Cfrac%7B5%7D%7B6%7D%29)
![1\frac{2}{35}x](https://tex.z-dn.net/?f=1%5Cfrac%7B2%7D%7B35%7Dx%3C3%5Cfrac%7B5%7D%7B6%7D)
Convert the mixed fraction
to an improper fraction. You can do this by multiplying 1 times 35 and adding 2.
![\frac{37}{35}x](https://tex.z-dn.net/?f=%5Cfrac%7B37%7D%7B35%7Dx%3C3%5Cfrac%7B5%7D%7B6%7D)
Now use the reciprocal (inverse fraction) and multiply on both sides to isolate x.
![(\frac{35}{37}) (\frac{37}{35})x](https://tex.z-dn.net/?f=%28%5Cfrac%7B35%7D%7B37%7D%29%20%28%5Cfrac%7B37%7D%7B35%7D%29x%20%3C%283%5Cfrac%7B5%7D%7B6%7D%29%28%5Cfrac%7B35%7D%7B37%7D%29)
![x](https://tex.z-dn.net/?f=x%3C3%28%5Cfrac%7B5%7D%7B6%7D%2A%5Cfrac%7B35%7D%7B37%7D%29)
![x](https://tex.z-dn.net/?f=x%3C3%28%5Cfrac%7B175%7D%7B222%7D%20%29)
![x](https://tex.z-dn.net/?f=x%3C3%5Cfrac%7B175%7D%7B222%7D)
Answer:
Helena gave the answer as (7y²z + 6yz²- 5 - 3yz² + 2) which is equivalent to (7y²z + 3yz² - 3).
Step-by-step explanation:
Misha's group was asked to write an expression equivalent to
7y²z + 3yz² - 3
When Mr. Chen checked their answers, he found only one to be correct.
And she was Helena.
Helena gave the answer as (7y²z + 6yz²- 5 - 3yz² + 2) which is equivalent to (7y²z + 3yz² - 3).
Because, (7y²z + 6yz²- 5 - 3yz² + 2)
= 7y²z + (6yz² - 3yz²) - (5 - 2)
= 7y²z + 3yz² - 3 (Answer)
Answer:
so good
Step-by-step explanation:
so good
Answer:
Sure, what do you need
Step-by-step explanation:
Thank you for posting your question here at brainly. I hope the answer will help you. Feel free to ask more questions.
<span>(t) = 0 gives
</span><span>-24t + 60 = 0
</span><span>t = 2.5
</span><span>For this t, the second derivative s"(t) = -24 is negative. And so, s(t) is maximum for t = 2.5.
</span><span>Maximum height is S = -12(2.5)^2 + 60(2.5) +8 = 233ft</span>